Over a million students use our free study notes to help them with their homework
0 = ex-1+ x - 6 ex-1 = 6-x x-1 = ln (6-x) -> here we have taken the natural log of both sides, but it only shows on one side as the natural log of e is 1.x = ln (6-x) + 1Question ...
Only the terms which will form the x4 term need to be considered:x * 2x2 * x + x * -3x * 3x2 = -7x4Therefore the answer is -7.
We need to use Newtons law F=ma going down the slope. We can see that the only forces acting in this direction are the component of the weight and friction, so we have that: F = Wsin30 - μR = 3a
( sec2(x))/((sec(x)+1)(sec(x)-1))Then, by the rule of 'difference of two squares', we know that this equals= (sec2(x))/(sec2(x)-1)= (sec2x/tan2x)s...
You cannot work with this equation in the current form so you must use identities to find an equivalent form that you can work with. It is known that tan(2A) = 2tan(A) / 1-tan2(A) so set this e...
←
339
340
341
342
343
→
Internet Safety
Payment Security
Cyber
Essentials